ALIGNMENT OF THE SERBIAN CIVIL SERVICE LEGISLATION WITH THE EU ACCESSION REQUIREMENTS - Vukašinović Radojičić, Zorica; Rabrenović, Aleksandra (EU and comparative law issues and challenges series (ECLIC), 2018)
The objective of the paper is to assess the degree of alignment of key aspects of the Serbian civil service legislation with the EU accession requirements. As Serbia aspires to become the EU member state, it is important that its civil service legislation is aligned the EU accession requirements, which should ensure civil service effectiveness during the negotiation process and subsequently within the EU system. Special attention in the paper is paid to the assessment of civil service professional development rules and practices, which include civil servants training, performance appraisal and promotion. The authors argue that the Serbian civil service legislation which governs professional development is still not fully aligned with the EU accession standards. In spite of the fact that the normative-legal framework mainly reflects the EU requirements, its level of implementation and effectiveness is not satisfactory. The authors conclude that additional legal and socio-political changes need to take place in order to achieve progress in this area.